Phonological Treatment Options for Children with Expressive Language Impairment - Hoover, Jill R. (Seminars in Speech and Language, 2019)
The vast majority of treatment efficacy research in the area of phonology focuses on issues relevant to children who have significant limitations in productive phonology but are “typically developing” in most other ways. The base of evidence to guide clinicians on planning intervention for children with phonological and cooccurring expressive language difficulties (PD + LI) is less well developed. Thus, the goal of this paper is to summarize the evidence on two treatment procedures designed to facilitate growth in phonological inventory for children who also require direct intervention to target other aspects of expressive language. We first review what is known about the delicate interaction between phonology and grammatical morphology. We focus the remainder of the summary on what is known about how to best address the more complex needs of children with PD + LI in intervention.
Keywords: intervention; phonology; syntax; morphology; comorbidity